CREATIVITY OF KEY COMPETENCIES AS A BASIS FOR INCREASING THE COMPETITIVENESS OF MODERN BUSINESS STRUCTURES (Development Service Industry Management, 2025)
The concept and key features of the competitiveness of business structures are defined. It has been determined that one of the key factors determining the competitive advantage of a business structure is the management skills of its management. The principles of effective management of the competitiveness of business structures are considered. The concept, role and key features of creativity in the context of increasing the competitiveness of modern business structures are defined. It is determined that creativity involves the ability to think outside the usual solutions, to make risky but reasonable decisions, and to create new business opportunities. It has been determined that the introduction of creativity in the management of a business structure allows to make the most efficient use of existing competencies and open up new development opportunities. The main directions of creativity management within the framework of key competencies are identified. The methods and tools based on the creativity of key competencies are considered. The elements of the structure of competitiveness based on creativity are defined. The challenges faced by the integration of creativity in the management of key competencies are highlighted. The elements of the system of effective management of the competitiveness of a business structure based on creativity are defined.
Keywords: creativity; key competencies; increasing the competitiveness; business structure; enterprise; system; integration